Respostas

2014-02-01T14:02:07-02:00
a + b + c = 1590

a=.b
     4

b= .c
    5

c= b
5

4c =5b

c = 5.b 
      4

substituindo em:

a + b + c = 1590 

b + 4 . 5 b  + 5.b
 4      5   4         4

3.b + b + 5.b = 1590               m,m,c( 4, 1) = 4
4             4

3.b + 4.b + 5.b = 1590. 4
12b= 6360
 b = 6360
         12
b= 530

substituindo b= 530 fica:

a =.b
     4
a =  3 * 530
      4
a1590 
       4
a = 397,50

c= 5.b
     4
c= 5 * 530 
       4
c=  2650
       4
c= 662,50

resposta:
 
a = 397,50
 b= 530
 c= 662,50
1 1 1